Anticariogenic properties and effects on periodontal structures of Stevia rebaudiana Bertoni. Narrative review - Soledad Contreras (Universidad de Concepción., 2013)
Introduction: Stevia rebaudiana Bertoni is a natural non-caloric sweetener, with more sweetness than sucrose, without adverse effects, which has demonstrated to have multiples benefits to the systemic health and recently to the oral health. This review's objective is to describe anti-cariogenic and anti-periodontophatics properties of its extracts. Results: Stevioside and rebaudioside A are the most important glycosides of the Stevia and none is cariogenic. In vitro researches have shown that Stevia extracts have anti-bacterial activity on Streptococcus mutans, Streptococcus sobrinus and Lactobacillus acidophilus, organisms that are closely related to the production and development of tooth decay. In vivo and in vitro it has been observed that the production of bacterial acids decrease attributing it a low acidogenic potential and a lesser effect of the demineralization of the enamel in comparison with others sweeteners. Furthermore, in vivo it has been proved an anti-plaque effect mainly due to a decrease in the production of bacterial insoluble polymers. These characteristics in combination with anti-inflammatory properties could result potentially effective in the treatment of periodontal diseases in significant numbers, as it has been observed in studies conducted in animals. Conclusion: Stevia presents properties that potentially are anti-caries and anti periodontal-diseases. However, in vivo studies are necessary to confirm these assumptions and provide a greater understanding of the mechanisms of action of this plant and the components involved. Notwithstanding, with the existing background, this sweetener can be postulated as a potential therapeutic complement in the odontological care, especially in patients that present base conditions such as obesity, diabetes and high blood pressure.